New Insights in Trigeminal Anatomy: A Double Orofacial Tract for Nociceptive Input - Henssen, Dylan J. H. A.; Kurt, Erkan; Kozicz, Tamas; van Dongen, Robert; Bartels, Ronald H. M. A.; van Cappellen van Walsum, Anne-Marie (Frontiers in Neuroanatomy, 2016)
Orofacial pain in patients relies on the anatomical pathways that conduct nociceptive information, originating from the periphery towards the trigeminal sensory nucleus complex (TSNC) and finally, to the thalami and the somatosensorical cortical regions. The anatomy and function of the so-called trigeminothalamic tracts have been investigated before. In these animal-based studies from the previous century, the intracerebral pathways were mapped using different retro- and anterograde tracing methods. We review the literature on the trigeminothalamic tracts focusing on these animal tracer studies. Subsequently, we related the observations of these studies to clinical findings using fMRI trials. The intracerebral trigeminal pathways can be subdivided into three pathways: a ventral (contralateral) and dorsal (mainly ipsilateral) trigeminothalamic tract and the intranuclear pathway. Based on the reviewed evidence we hypothesize the co-existence of an ipsilateral nociceptive conduction tract to the cerebral cortex and we translate evidence from animal-based research to the human anatomy. Our hypothesis differs from the classical idea that orofacial pain arises only from nociceptive information via the contralateral, ventral trigeminothalamic pathway. Better understanding of the histology, anatomy and connectivity of the trigeminal fibers could contribute to the discovery of a more effective pain treatment in patients suffering from various orofacial pain syndromes.